1999
DOI: 10.1037/0096-1523.25.5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Decision processes in discrimination: Fundamental misrepresentations of signal detection theory.

Abstract: A new approach to studying decision making in discrimination tasks is described that does not depend on the technical assumptions of signal detection theory (e.g., normality of the encoding distributions). In 3 different experiments, results of these new distribution-free tests converge on a single, surprising conclusion: response biases had substantial effects on the encoding distributions but no effect on the decision rule, which was uniformly unbiased in equal and unequal base rate conditions and in symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
118
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(122 citation statements)
references
References 24 publications
0
118
2
2
Order By: Relevance
“…Inspection of Balakrishnan's (1998aBalakrishnan's ( , 1998bBalakrishnan's ( , 1999) U R (k) curves confirms that they are generally flat-topped, much like the SDT predictions in Figure 5. Nevertheless, from such evidence, Balakrishnan (1999) has concluded that the decision rule in his experiments was uniformly unbiased despite payoff and base rate manipulations.…”
Section: New Measures Of Responsementioning
confidence: 52%
See 4 more Smart Citations
“…Inspection of Balakrishnan's (1998aBalakrishnan's ( , 1998bBalakrishnan's ( , 1999) U R (k) curves confirms that they are generally flat-topped, much like the SDT predictions in Figure 5. Nevertheless, from such evidence, Balakrishnan (1999) has concluded that the decision rule in his experiments was uniformly unbiased despite payoff and base rate manipulations.…”
Section: New Measures Of Responsementioning
confidence: 52%
“…Nevertheless, from such evidence, Balakrishnan (1999) has concluded that the decision rule in his experiments was uniformly unbiased despite payoff and base rate manipulations. He concludes that "this seemingly paradoxical result is fundamentally inconsistent with the entire family of signal detecton theory models, raising some important questions about the significance of many published results" (Balakrishnan, 1999(Balakrishnan, , p. 1189. The logic of this argument is that of accepting the null hypothesis.…”
Section: New Measures Of Responsementioning
confidence: 99%
See 3 more Smart Citations